2001
DOI: 10.1101/gad.899601
|View full text |Cite
|
Sign up to set email alerts
|

The languages of bacteria

Abstract: Bacteria communicate with one another using chemical signaling molecules as words. Specifically, they release, detect, and respond to the accumulation of these molecules, which are called autoinducers. Detection of autoinducers allows bacteria to distinguish between low and high cell population density, and to control gene expression in response to changes in cell number. This process, termed quorum sensing, allows a population of bacteria to coordinately control the gene expression of the entire community. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
304
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(310 citation statements)
references
References 105 publications
(125 reference statements)
4
304
0
2
Order By: Relevance
“…Pure fractions were identified by electrospray ionization-MS on a Sciex API-150EX single quadrupole mass spectrometer (DP 10 V, FP 50 V) operated in multichannel analysis mode, pooled, and lyophilized. In all cases, the homogeneity of pure pooled products was verified by analytical reverse-phase HPLC using a C4-functionalized Vydac 218TP5415 column running a gradient of 20-80% B over 30 min; 1 . The cells were harvested by centrifugation and resuspended in BugBuster (50 ml; Novagen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure fractions were identified by electrospray ionization-MS on a Sciex API-150EX single quadrupole mass spectrometer (DP 10 V, FP 50 V) operated in multichannel analysis mode, pooled, and lyophilized. In all cases, the homogeneity of pure pooled products was verified by analytical reverse-phase HPLC using a C4-functionalized Vydac 218TP5415 column running a gradient of 20-80% B over 30 min; 1 . The cells were harvested by centrifugation and resuspended in BugBuster (50 ml; Novagen).…”
Section: Methodsmentioning
confidence: 99%
“…T he term ''quorum sensing'' has been coined to describe the ability of a population of unicellular bacteria to act as a multicellular organism in a cell-density-dependent manner; that is, a way to sense ''how many are out there'' (1)(2)(3). Bacteria use small diffusible molecules to exchange information among themselves (2).…”
mentioning
confidence: 99%
“…1C), which was homologous to the consensus sequence of σ 70 promoter of C. jejuni (25), was found in the upstream region of the transcriptional start site of cdtA. Since there have been many reports on the relationship between quorum sensing and expression of toxin genes in some pathogens (22), primer extension assay was performed to investigate if a luxS mutation may have an effect on the cdt transcription in C. jejuni. The results showed that the amount of cdt transcripts in the luxS mutant was approximately 61% of that in the wildtype (Fig.…”
Section: Primer Extension Assaymentioning
confidence: 99%
“…In this study we performed simulations for concentrations of different species (biological entities in our model) involved in competence as well as sporulation pathways. We targeted only those QS phenotypes for which the genetic organization and molecular characterization of the components are fully elucidated (Schauder and Bassler 2012;Mader et al 2012). We proposed a simple model to represent competence and virulence phenotypes and to determine pathway steps to limit the flux of the molecular processes.…”
Section: Introductionmentioning
confidence: 99%